A dangerous causative microorganism of early onset neonatal sepsis: Stenotrophomonas maltophilia. Two case reports and a review of the literature. (12th December 2022) - Mutlu, Mehmet; Kader, Şebnem; Aslan, Yakup
Abstract: Stenotrophomonas maltophilia ( S. maltophilia ) is an important aerobic, non-fermentative, Gram-negative, multidrug resistant organism. Although this microorganism is frequently reported as a causative agent of nosocomial infections in neonatal intensive care unit, a few cases were reported about as a causative microorganism of early-onset neonatal sepsis (EONS). We report two cases with EONS caused by S. maltophilia and also, we reviewed the EONS reported caused by S. maltophilia .